Advanced Frequency Modulation Control Strategy For Wind-Storage Hybrid Systems Utilizing Enhanced Virtual Synchronous Generator Technology - Wang Chuntian; Jing Lantao; Zhang Bin; Zhang Qiang; Wang Chao; Dai Xu (SHS Web of Conferences)
A combined wind and energy storage frequency modulation control strategy is proposed to alleviate the frequency instability problem caused by large-scale wind power grid integration. Because of the great influence of wind speed, the frequency modulation capability of doubly-fed wind turbines cannot satisfy the frequency regulation requirement. The energy storage that is used to make up for the inadequacy of the wind turbine’s self-frequency regulation has characteristics such as fast response speed and high controllability. When there is frequency fluctuation in the system, the output power of the wind turbine is optimized by virtual inertia control. The comparative analysis of frequency characteristics of the power system under wind power without frequency regulation, wind power frequency regulation, and wind power storage combined frequency regulation performed in the MATLAB/Simulink simulation platform shows that the combination of wind power with storage can greatly improve the frequency stability of the power system.